2006
DOI: 10.1002/cne.20981
|View full text |Cite
|
Sign up to set email alerts
|

Time course of substance P expression in dorsal root ganglia following complete spinal nerve transection

Abstract: Recent evidence suggests that substance P (SP) is up-regulated in primary sensory neurons following axotomy and that this change occurs in larger neurons that do not usually produce SP. If this is so, then the up-regulation may allow normally neighboring, uninjured, and nonnociceptive dorsal root ganglion (DRG) neurons to become effective in activating pain pathways. By using immunohistochemistry, we performed a unilateral L5 spinal nerve transection on male Wistar rats and measured SP expression in ipsilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 90 publications
(98 reference statements)
2
43
0
Order By: Relevance
“…Initially, an increase is found in the number of both small and large diameter DRG neurons expressing SP (Neumann et al 1996;Weissner et al 2006). However, in the nerve injury models this primary increase later tend to decrease below basal levels for small diameter DRG neurons (Neumann et al 1996;Weissner et al 2006). With time, the decreased spinal levels of SP may be partially recovered (Himes and Tessler 1989).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Initially, an increase is found in the number of both small and large diameter DRG neurons expressing SP (Neumann et al 1996;Weissner et al 2006). However, in the nerve injury models this primary increase later tend to decrease below basal levels for small diameter DRG neurons (Neumann et al 1996;Weissner et al 2006). With time, the decreased spinal levels of SP may be partially recovered (Himes and Tessler 1989).…”
mentioning
confidence: 93%
“…These models have shown that the expression levels of the primary afferent neurotransmitters change in response to the painful insult. Initially, an increase is found in the number of both small and large diameter DRG neurons expressing SP (Neumann et al 1996;Weissner et al 2006). However, in the nerve injury models this primary increase later tend to decrease below basal levels for small diameter DRG neurons (Neumann et al 1996;Weissner et al 2006).…”
mentioning
confidence: 95%
“…Here we focused on the neuropeptide, substance P, because it is essential for pain signaling between the dorsal root ganglion (DRG) cells and the spinal cord dorsal horn (McLeod et al 1999;Otsuka and Yanagisawa, 1990;Weissner et al, 2006) and there is limited direct comparison of its relative involvement in mechanical and/or inflammatory insults that produce pain. In peripheral nerve injury, recruitment of macrophages is required for myelin clearance and axonal regeneration Perry et al, 1987) and their secreted inflammatory mediators are highly associated with the pathogenesis of neuropathic pain (Marchand et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, treating Schwann cell culture alone (b) with DETA-NO caused a significant reduction in PPTA gene expression (***<p=0.0001 compared to vehicle) survival and maintenance of all the subset of DRG neurons, it interacts specifically with nociceptive sensory neurons (see review by Lewin and Mendell 1993), which are trkA, SP, and CGRP positive (Qian et al 1996). Incidentally, absence of NGF from postnatal DRG cultures or axotomy increases nNOS expression in the majority of these nociceptive neurons (Zhang et al 1993;Thippeswamy and Morris 1997a;Renganathan et al 2000;Thippeswamy et al 2001bThippeswamy et al , 2005b in addition to a few large neurons, which may also express SP (Malcangio et al 2000;Weissner et al 2006). Recent evidence suggests that in absence of trkA signaling, NO protects neurons intrinsically by taking over the downstream of NGF-trkA signaling pathway (Culmsee et al 2005;Akassoglou 2005).…”
Section: Discussionmentioning
confidence: 95%
“…Nitric oxide synthase (NOS) catalyze the formation of NO from the substrate L-arginine. In addition to nNOS, galanin and vasoactive intestinal peptide (VIP) are also up-regulated, while substance P (SP) and calcitonin gene-related peptide (CGRP) are downregulated in DRG after axotomy (Doughty et al 1991;Verge et al 1995;Thippeswamy et al 2001aThippeswamy et al , 2007. However, there has been a variation in up-or downregulation of SP after axotomy, which depends on the type/ site and duration of nerve injury and the subpopulation of DRG neurons (Malcangio et al 2000;Siri et al 2001;Wallin and Schott 2002;Weissner et al 2006). SP is known to modulate nociception at the spinal level (Malcangio et al 2000;De Vane 2001), and its expression is mediated by NGF (Wong and Oblinger 1991;Zhang et al 1995;Malcangio et al 2000;Gerard et al 2005).…”
mentioning
confidence: 97%